Leveraging risk and data analytics for sustainable management of buried water infrastructure. Issue 2 (27th April 2022) - Ganjidoost, Amin; Vladeanu, Greta; Daly, Craig Michael
Abstract: A proactive and sustainable asset management program is vital for utilities to maintain their capital assets at the required level of service, while ensuring that adequate funds are available for intervening when needed on their riskiest assets. One of the most popular methods for building such programs is by prioritizing capital investments based on the asset's risk of failure, which evaluates its likelihood or probability of failure and impact, or consequence of failure. This paper presents the application of a financial planning analysis using system dynamics to provide insights into quantifying more practical risk avoidance. This is exemplified through a 5‐year budgetary planning scenario analysis for a large‐sized US water utility to help the utility best plan for short and long‐term capital operations and show the value of a data‐driven and risk‐based decision‐making.